(untitled) (Journal of Geography and Environmental Management, 2018)
In this article, the intra-annual distribution of river runoff, determined by multi-year data from the rivers of the Esil basin, modified by anthropogenic influence, was calculated. Hydrological stations with long-term long data series were mainly selected. From 1933 to 2005, the river Esil – at the Astana station, 1974 – 2015, the river Esil – at the Turgenevka station, 1936 – 2015, the river Zhabay – at the Atbasar station and from 1973 to 2015, the Moiyldy river – at the Nikolaevka station was analyzed.The gaps in the series of annual and monthly water flow rates were restored by the analogy method. The impact of anthropogenic impact on the annual flow of the Astana River Sewage has been estimated. For calculation of the annual distribution of runoff the method of layout proposed by V. G. Andreyanov is applied With the available data by means of constructing an integral curve, periods of river runoff with different levels of economic activity were identified. Conditionally natural and disturbed periods of runoff are reconciled with each other.